Yaupon Psyllid Gyropsylla ilecis (Ashmead) (Insecta: Hemiptera: Aphalaridae) - Mark Wilhelm; Matthew Borden; Adam Dale (EDIS)
The yaupon psyllid, Gyropsylla ilecis (Ashmead), is a native insect of the family Psyllidae, order Hemiptera (Figure 1). The insect is inconspicuous during most of the year, but the leaf galls it produces in spring are more easily observed. Nymphs feed on the new growth of yaupon holly, Ilex vomitoria, causing leaves to deform into a protective gall. The yaupon holly, native to the southeastern United States, is used as an ornamental tree or shrub and has also been used for centuries to produce a caffeinated, tea-like beverage. The yaupon psyllid is considered a minor aesthetic pest due to the unsightly presence of galls and some stunting of twigs. However, yaupon holly is rarely severely damaged by this insect.